1995
DOI: 10.1126/science.7886454
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Serotonin-Controlled Behaviors by G o in Caenorhabditis elegans

Abstract: Seven transmembrane receptors and their associated heterotrimeric guanine nucleotide-binding proteins (G proteins) have been proposed to play a key role in modulating the activities of neurons and muscles. The physiological function of the Caenorhabditis elegans G protein Go has been genetically characterized. Mutations in the goa-1 gene, which encodes an alpha subunit of Go (G alpha o), cause behavioral defects similar to those observed in mutants that lack the neurotransmitter serotonin (5-HT), and goa-1 mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
282
1

Year Published

1996
1996
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 281 publications
(290 citation statements)
references
References 31 publications
7
282
1
Order By: Relevance
“…As in mammals, GOA-1 G o ␣ is ubiquitously expressed in the nervous system in C. elegans and reported to be involved in many aspects of behavior (21,22). In our study, we demonstrated that GOA-1 modulates sensory responses, specifically, olfactory adaptation (and salt chemotaxis plasticity) in C. elegans.…”
Section: Down-regulation Of Gq␣-dag Signaling By Go␣ Is Crucial For Omentioning
confidence: 53%
See 2 more Smart Citations
“…As in mammals, GOA-1 G o ␣ is ubiquitously expressed in the nervous system in C. elegans and reported to be involved in many aspects of behavior (21,22). In our study, we demonstrated that GOA-1 modulates sensory responses, specifically, olfactory adaptation (and salt chemotaxis plasticity) in C. elegans.…”
Section: Down-regulation Of Gq␣-dag Signaling By Go␣ Is Crucial For Omentioning
confidence: 53%
“…However, the mode of action of G o in these behaviors is unclear. C. elegans has 21 G protein ␣-subunit genes (19,20), and the only orthologue of mammalian G o ␣ is encoded by the goa-1 gene (21,22). Mutations in goa-1 cause various defects in behaviors, including locomotion and egg laying.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…One possible explanation for the observed specificity of heterotrimer subunit composition is a compartmentalization of the signal transduction elements in the plasma membrane of intact cells [26]. Nevertheless, the G~o subunit is currently without a specific effector-regulating function, though results obtained from modulating gene expression of the G~o gene in the roundworm Caenorhabditis elegans underline an important role of this G protein in various neuronal functions [51,52].…”
Section: Functions Of G Proteins On Organelle Membranesmentioning
confidence: 99%
“…In general, TA/OA oppose the action of serotonin (5-HT) [1]. For example, in the free-living nematode, Caenorhabditis elegans, exogenous TA or OA cause hyperactivity, inhibit pharyngeal pumping on bacteria or 5-HT and suppress 5-HT stimulated egg-laying [2][3][4]. The OA inhibition of pumping appears to involve Gα o , as OA inhibits the firing rate of the pharyngeal muscle in wild-type C. elegans, but has no effect on goa-1 mutants defective for Gα o function [5].…”
Section: Introductionmentioning
confidence: 99%